2021
DOI: 10.1002/agg2.20146
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and stability of five energycane cultivars at two latitudes in Georgia

Abstract: Energycane (Saccharum hybrid) could be a viable bioenergy crop for the Southeast United States. Five energycane cultivars were planted in 2008 at a northern (Watkinsville, GA) and a southern (Tifton, GA) site, and were grown for 7 yr to compare biomass yields. Plots were arranged in a four replicate randomized complete block design at each site. Energycane was grown under rainfed conditions with 90–112 kg ha–1 N applied annually. Plant height was recorded at least monthly, and stalks were sampled to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Furthermore, SH had a significant positive correlation with BY. Knoll et al [36] also observed that mature SH was highly correlated with biomass yield. Reduction in SH and SN under WS resulted in a reduction in plant biomass.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, SH had a significant positive correlation with BY. Knoll et al [36] also observed that mature SH was highly correlated with biomass yield. Reduction in SH and SN under WS resulted in a reduction in plant biomass.…”
Section: Discussionmentioning
confidence: 91%
“…Both energycane and sugarcane are highly polyploid, interspecific hybrids between Saccharum officinarum and Saccharum spontaneum , but energycane has a higher proportion of Saccharum spontaneum in its genome. This contributes to greater biomass yields, elevated resilience under marginal conditions, lower sugar, and higher fiber content in the stems of energycane relative to sugarcane [ 4 – 7 ]. Energycane’s superior resilience and biomass accumulation are supported by a more vigorous root system and higher light interception efficiency than sugarcane.…”
Section: Introductionmentioning
confidence: 99%
“…Biofuels produced by perennial feedstocks such as energycane will enhance energy independence, while contributing to carbon neutrality (Durrett et al., 2008; Field et al., 2020). Energycane, an interspecific hybrid in the genus Saccharum , produces exceptional biomass yields (Knoll et al., 2021). Developed alongside modern sugarcane cultivars in sugarcane breeding programs, energycane differs significantly from its close relative in several key traits (Alexander, 1985; Carvalho‐Netto et al., 2014; de Abreu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These attributes allow its growth on marginal lands and in more northern regions than sugarcane. Therefore, energycane has a larger potential footprint in the Southern United States than sugarcane, and decreased competition for land used in food production (de Abreu et al., 2020; Knoll et al., 2021; Matsuoka et al., 2014).…”
Section: Introductionmentioning
confidence: 99%